Characterization of the SPI-1 Type III Secretion System in Pseudomonas fluorescens 2P24 - Wang, Jing; Luo, Yuan; Gu, Yilin; Wei, Hai-Lei (Frontiers in Microbiology, 2021)
Pseudomonas fluorescens 2P24 is a plant growth-promoting rhizobacterium (PGPR) isolated from wheat take-all decline soil. Genomic analysis of strain 2P24 revealed the presence of a complete SPI-1 type III secretion system (T3SS) gene cluster on the chromosome with an organization and orientation similar to the SPI-1 T3SS gene clusters of Salmonella enterica and P. kilonensis F113. Phylogenetic analysis revealed that the SPI-1 T3SS gene cluster of strain 2P24 might be obtained from Salmonella and Shigella by horizontal gene transfer. Two transcriptional regulator homologs of HilA and InvF were found from the SPI-1 T3SS gene cluster of strain 2P24. HilA regulated the expression of the structural genes positively, such as invG, sipB, sipD, prgI, and prgK. Prediction of transcriptional binding sites and RNA-seq analysis revealed 14 genes were up-regulated by InvF in strain 2P24. Exploring potential roles of SPI-1 T3SS revealed that it was not associated with motility. However, 2P24ΔinvF reduced resistance against Fusarium graminearum significantly. 2P24ΔhilA enhanced formation of biofilm significantly at 48 h. All three mutants 2P24ΔhilA, 2P24ΔinvF, and 2P24ΔinvE-C reduced the chemotactic responses to glucose significantly. Finally, the determination of SPI-1 mutants to trigger innate immunity in Nicotiana benthamiana showed that 2P24ΔinvE-C reduced the ability to induce production of reactive oxygen species compared to the wild type strain 2P24.